Corrigendum to “Monitoring elasmobranch fisheries via social media in data-poor regions and conflict zones: The Gaza Strip as a case study” [Ocean Coastal Manag. 279 (2026) 108250] - Re'em Neri; Adi Barash; Uri Roll; Nadav Shashar (Ocean & Coastal Management, 2026)

Monitoring elasmobranch fisheries via social media in data-poor regions and conflict zones: The Gaza Strip as a case study - Re'em Neri; Adi Barash; Uri Roll; Nadav Shashar (Ocean & Coastal Management, 2026)

Whale sharks (Rhincodon typus) in the Mediterranean Sea: first confirmed records from the southeastern Levant - ADI BARASH; YA’ARA GROSSMARK; RE’EM NERI; SHEVY BAT-SHEVA ROTHMAN (Mediterranean Marine Science, 2026)
The whale shark (Rhincodon typus) is the largest living fish species and a cosmopolitan planktivore primarily inhabiting tropical and warm-temperate waters. In most checklists it is generally considered absent from the Mediterranean Sea, although isolated sightings have been reported in recent years. Here we present the first confirmed records of R. typus from the southeastern Levantine coast, with multiple observations of two distinct individuals between September and November 2025. These sightings are added to the few existing records from Turkey (Samandağ, Hatay, 2021) and Spain (Ceuta, Strait of Gibraltar, 2022). They also raise questions regarding the species’ distribution across the Mediterranean and the origin of these individuals, which may have entered through the Suez Canal (Lessepsian migration) or from the Atlantic Ocean via the Strait of Gibraltar. These records may reflect ongoing changes in the Mediterranean Sea and highlight the importance of continued monitoring.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Incorporation of human–wildlife interactions in ecosystem‐based management to enhance conservation of endangered guitarfish - Yaara Grossmark; Barak Azriali Zohar; Adi Barash; Michelle E. Portman (Conservation Biology, 2024)
Growing human use of the marine environment increases the proximity of humans to marine wildlife and thus likely increases human–wildlife interactions. Such interactions influence perceptions of nature and promote or undermine conservation. Despite their importance, human–wildlife interactions are rarely considered in ecosystem‐based marine spatial planning (MSP). Ideally, these interactions should be identified and considered in ecosystem‐based management (EBM), which is often purported to be the basis for MSP. We used Marxan software and data from a citizen science project documenting location, species, age, sex, and activity type to identify regions along Israel's coast with a high probability of encounters between people and 2 species of guitarfish. We considered the geographic distribution of these encounters and the various activities undertaken by the reporting observers. We ran 4 scenarios in Marxan. Two had conservation goals of 30% and 50% guitarfish habitat protection. In the third and fourth scenarios, we added a 50% conservation goal of human leisure activities to each guitarfish conservation goal. We also conducted a gap analysis between our guitarfish conservation goals and the Israel Nature and Parks Authority's master plan for marine protected areas. We found the park authority was close to meeting the 30% goal but was far from meeting the conservation goal of 50% of guitarfish habitat conservation. Different human uses were more likely to interact with different life stages of guitarfish, and different recreational activities occurred in different areas. Identifying areas of specific human use showed which activities should be addressed in conservation management decisions. Our addition of certain recreational uses to the model of habitat conservation showed how enhancing human dimensions in conservation planning can lead to more holistic ecosystem‐based conservation necessary for effective marine planning.

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Characterising a potential nearshore nursery ground for the blackchin guitarfish (Glaucostegus cemiculus) in Ma’agan Michael, Israel - Barak Azrieli; Eynav Cohen; Leigh Livne; Debra Ramon; Anat Tsemel; Eyal Bigal; Eli Shemesh; Ziv Zemah-Shamir; Adi Barash; Dan Tchernov; Aviad Scheinin (Frontiers in Marine Science, 2024)
The blackchin guitarfish Glaucostegus cemiculus has suffered severe declines and regional extirpation throughout its known distributions. While this species and its relative, the common guitarfish Rhinobatos rhinobatos , have been described in the Mediterranean Sea with co-occurring habitat ranges, no research has recorded the existence or extent of these two separate populations along the Israeli coastal waters. Along a particular coast in Israel, Ma’agan Michael, fishermen have reported annual observations of juvenile guitarfish between June to November for the last forty years. Based on these citizen-based observations the main research objective is to establish whether Ma’agan Michael fulfils all three criteria from the literature by Dr Michelle Heupel, allowing it to be acknowledged as a nursery ground for G. cemiculus . The methodology built for this objective integrates biological characteristics data with the identification of a recurrent seasonal distribution. Visual surveys exhibited a significantly higher abundance in Ma’agan Michael when compared to an adjacent area (Caesarea), with 2,096 recorded observations overall. Additionally, using a species-specific modified Catch and Release protocol, a total of 492 juveniles were captured with a beach seine net. During these capturing events, individuals were morphometrically measured and sampled for future genetic analyses. Out of these, 327 specimens were also fitted for PIT tags to track recaptures in subsequent captures. The highest abundance of neonates was caught from August to September each year (2017–2019), and all individuals captured during this study were identified in the field as G. cemiculus , ranging from 20–35 cm in length (85% of captures). Many specimens had an umbilical cord scar (n = 88), with a large percentage possessing visual remains of the yolk sac. For the first time, this study provides an inter-year description of the species Glaucostegus cemiculus present along the Israeli shoreline.

Some Like It Hot: Investigating Thermoregulatory Behavior of Carcharhinid Sharks in a Natural Environment with Artificially Elevated Temperatures - Adi Barash; Aviad Scheinin; Eyal Bigal; Ziv Zemah Shamir; Stephane Martinez; Aileen Davidi; Yotam Fadida; Renanel Pickholtz; Dan Tchernov (Fishes, 2023)
Global warming raises seawater temperatures and creates changes which have been found to affect the movement of large migrating marine species. Understanding the thermal niches of marine species could prove essential to anticipate how the future climate will alter migrations, and how conservation efforts will have to change accordingly. Orot Rabin power station in Hadera, Israel uses seawater to cool its turbine and releases the warm water back into the Mediterranean Sea. As a result, a marine area with artificially elevated temperatures is created around the effluent. Every winter in the past two decades, this area attracts sharks of two species, Carcharhinus obscurus and Carcharhinus plumbeus, presumably to spend the cold months at a higher temperature. This study concentrated on this point of artificial heat dissipation, which maintains a wide gradient of surface temperatures and allowed us to examine the temperature preferences of these species when given a larger range than what is naturally found in the sea. Between 2016 and 2018, 16 sharks were tagged with acoustic tags, 3 of which had temperature sensors, and 2 were additionally tagged with pop-up archival tags also logging temperature data. Results show that the sharks stayed in the elevated temperature, while the ambient sea was cold during the winter, spending several months in the heated area. Both species displayed a similar preferred range, spending 90 percent of their time at a temperature between 21.8 °C and 26.1 °C while the surrounding sea was 15.5–25.5 °C. Considering this chosen thermal niche and the rise in water temperature, it appears that for the past 40 years, the Eastern shores of the Mediterranean have become more suitable for these species, especially during transitional seasons. The question that arises, however, is whether these shark populations will benefit from the expanding range of preferable temperatures, or whether their proximity to shorelines will put them at greater risk in terms of human activities such as fishing and pollution.

Depth Partitioning and Diel Movement of Two Large Carcharhinid Sharks in Extremely Shallow Waters - Adi Barash; Aviad Scheinin; Eyal Bigal; Ziv Zemah Shamir; Stephane Martinez; Dan Tchernov (Fishes, 2023)
Two species of carcharhinid sharks aggregate every winter at the warm water effluent of a coastal power plant on the Israeli Mediterranean coast. The two species (Carcharhinus obscurus and Carcharhinus plumbeus) cooccur in a highly confined area for several months every year and are highly associated with the area in and around the hot water effluent. Niche partitioning has recently been suggested as a mechanism that enables the coexistence of similar shark species by resource partitioning, spatial partitioning, and temporal partitioning. In this study, we used acoustic telemetry to study the individual diel movement and activity patterns within this enclosed area and examined the differences between the two species sharing it. Although this location only reaches a maximum depth of 7.5 m, we found both species perform a diel vertical movement, rising closer to the surface at night and moving deeper during daytime. Furthermore, the two shark species swam at different depths both day and night, with C. obscurus swimming in the upper column, about 2 m shallower than C. plumbeus. The very small scale of movement, which nearly equals the sharks’ body length, suggests movement patterns might be conserved at the species level. Moreover, spatiotemporal differences between the two species may reflect a mean of interspecific partitioning that occurs even in a highly confined and shallow habitat.

An Updated Greek National Checklist of Chondrichthyans - Ioannis Giovos; Roxani Naasan Aga-Spyridopoulou; Fabrizio Serena; Alen Soldo; Adi Barash; Nikolaos Doumpas; Georgios A. Gkafas; Dimitra Katsada; George Katselis; Periklis Kleitou; Vasileios Minasidis; Yannis P. Papastamatiou; et al. (Fishes, 2022)
Accurate checklists of species are essential for evaluating their conservation status and for understanding more about their distribution, biology and ecology and, therefore, the first step in order to effectively protect them. According to the existing literature, the Greek seas are rich in chondrichthyan biodiversity and herein, we update the most recent chondrichthyan checklist for the country regarding the species that are present in the Greek waters, correct unvalidated miscellaneous sightings and observations and provide guidelines about future research to improve their conservation. In total, 330 sources were collected from which 276 were used for further analysis, resulting in 1485 records of 67 species, among which 61 are confirmed by experts, including 34 sharks, 26 batoids and one chimaera. We are further listing six species as “Questionable/Not Confirmed”.

Integrating Literature, Biodiversity Databases, and Citizen-Science to Reconstruct the Checklist of Chondrichthyans in Cyprus (Eastern Mediterranean Sea) - Ioannis Giovos; Fabrizio Serena; Dimitra Katsada; Athanasios Anastasiadis; Adi Barash; Charis Charilaou; Jason M. Hall-Spencer; Fabio Crocetta; Alexander Kaminas; Demetris Kletou; Mary Maximiadi; Vasileios Minasidis; et al. (Fishes, 2021)
Chondrichthyans are apex predators influencing the trophic web through a top-down process thus their depletion will affect the remaining biota. Notwithstanding that, research on chondrichthyans is sparse or data-limited in several biogeographic areas worldwide, including the Levantine Sea. We revise and update the knowledge of chondrichthyans in Cyprus based on a bibliographic review that gains information retrieved from peer-reviewed and grey literature, Global Biodiversity Information Facility (135 records of at least 18 species) and the Ocean Biodiversity Information System (65 records of at least14 species), and the citizen science project Mediterranean Elasmobranchs Citizen Observations (117 records per 23 species). Our updated checklist reports 60 species that account for about 70% of the Mediterranean chondrichthyan biota. The list includes 15 more species than the previous checklist and our study reports three new species for Cyprus waters, namely the blackmouth catshark Dalatias licha, the round fantail stingray Taeniurops grabatus, and the sawback angelshark Squatina aculeata. Our research highlights the need for conservation measures and more studies regarding the highly threatened blackchin guitarfish Glaucostegus cemiculus and the devil ray Mobula mobular, and stresses the importance for training a new generation of observers to strengthen the knowledge and conservation of elasmobranchs in the region.

MEDLEM database, a data collection on large Elasmobranchs in the Mediterranean and Black seas - CECILIA MANCUSI; ROMANO BAINO; CATERINA FORTUNA; LUIS GIL DE SOLA; GABRIEL MOREY; MOHAMED NEJMEDDINE BRADAI; ARGYRIOS KALLIANOTIS; ALEN SOLDO; FARID HEMIDA; ADIB ALI SAAD; MARK DIMECH; PANAGIOTA PERISTERAKI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean Large Elasmobranchs Monitoring (MEDLEM) database contains over 3000 records (more than 4000 individuals) of large elasmobranch species from 20 different countries around the Mediterranean and Black seas, observed from 1666 to 2017. The main species included in the archive are the devil fish (1 813 individuals), the basking shark (939 individuals), the blue shark (585 individuals) and the great white shark (337 individuals).In the last decades other species such as the shortfin mako (166 individuals), the spiny butterfly ray (138) and the thresher shark (174 individuals) were reported with an increasing frequency. This was possibly due to an increased public awareness on the conservation status of sharks, and a consequent development of new monitoring programmes. MEDLEM does not have a homogeneous reporting coverage throughout the Mediterranean and Black seas and it should be considered as a database of observed species presence. Scientific monitoring efforts in the south-eastern Mediterranean and Black seas are generally lower than in the northern sectors and the absence in our database of some species does not imply their actual absence in these regions. Some considerations are made on the frequency and spatial distribution of records, size structure of the observed individuals for selected species, general area coverage and species involved as by-catch by fishing gear.

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Abstracts of Papers Presented at the Japan-Israel Workshop on Novel Approaches for Controlling Insect Pests and Plant Diseases Binational Plant Protection Cooperation - I. Yamamoto; I. Ishaaya; A. R. Horowitz; Shinzo Kagabu; Akinori Hirashima; E. Shaaya; M. Kostjukovsky; K. R. S. Ascher; D. Veierov; N. Aharonson; E. Kleter; Miriam Eliyahu; et al. (Phytoparasitica, 1997)